Transforming research recruitment: Leveraging EHR systems and patient portals - Megan Schwinne; Edward Woods; Barney Chan; Candace D. Speight; Vivian Corry; Neal W. Dickert; Gabriel R. Najarro (Journal of Clinical and Translational Science)
Electronic health records and patient portals are increasingly utilized to enhance research recruitment efficiency, yet response patterns across patient groups remain unclear. We examined 10 studies at Emory Healthcare that used these tools to identify and recruit 24,000 patients over 1 year. Response rates were lower among males and Black individuals, though study interest was higher among respondents. Interest was also greater among those with frequent healthcare interactions and lower comorbidity. In a large academic health system, portal-based recruitment offered a streamlined approach to research recruitment and patient engagement, with minor variations across patient characteristics warranting continued study.